2011
DOI: 10.2140/jomms.2011.6.51
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical characterization of mixed fractal structures

Abstract: It is because of people like Marie-Louise and Charles that it is worth fighting for a better world.We present a new technique to determine the fractal or self-similarity dimension of a sequence of curves. The geometric characterization of the sequence is obtained from the mechanical properties of harmonic oscillators with the same shape of the terms composing the given sequence of curves. The definition of "dynamical dimension" is briefly introduced with the help of simple examples. The theory is proved to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…With the dynamical approach it is possible to determine the fractal dimension of a given sample by exploring variables that are not accessible to classical methods. In [6][7][8][9] it was shown that the dynamical dimension of a sequence of subsamples obtained by successively cutting the previous one from the original sample led to its fractal dimension.…”
Section: The Inverse Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…With the dynamical approach it is possible to determine the fractal dimension of a given sample by exploring variables that are not accessible to classical methods. In [6][7][8][9] it was shown that the dynamical dimension of a sequence of subsamples obtained by successively cutting the previous one from the original sample led to its fractal dimension.…”
Section: The Inverse Problemmentioning
confidence: 99%
“…This non-homogeneous distribution of the bending moment leads to the inclusion of a disturbance term Ω k in the determination of the period of oscillation. It can be shown that for regular fractal curves the term Ω k → 1 for large values of k [6][7][8][9]. Therefore the angular coefficients of the straight lines corresponding to the functions log(T k /T0) × log(λ k /L0) for the three initial conditions M, H and V are related with the Hausdorff dimension as DM = DH = DV = (1 − F )/2 since all three angular coefficients coincide for the cases under consideration, FM = FH = FV = F .…”
Section: Introductionmentioning
confidence: 99%